1985
DOI: 10.1021/ic00212a006
|View full text |Cite
|
Sign up to set email alerts
|

Thioether, thiolato, and 1,1-dithioato complexes of bis(2,2'-bipyridine)ruthenium(II) and bis(2,2'-bipyridine)osmium(II)

Abstract: Die Redoxeigenschaften und die spektralen Eigenschaften der cis‐Ru‐Komplexe (I) und der cis‐Os‐Komplexe (II) werden im Hinblick auf den relativen n‐Säure‐Charakter der S‐, N‐, P‐enthaltenden Liganden sowie der Halogenidliganden rationalisiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
67
0
4

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 7 publications
15
67
0
4
Order By: Relevance
“…It is known that Ru-bpy complexes can coordinate thioethers [42]. Recently, we found that these ligands can also be photoreleased with very high efficiency.…”
Section: Ru-bpy Complexes Poor Donor Ligands and Genetic Inducersmentioning
confidence: 97%
“…It is known that Ru-bpy complexes can coordinate thioethers [42]. Recently, we found that these ligands can also be photoreleased with very high efficiency.…”
Section: Ru-bpy Complexes Poor Donor Ligands and Genetic Inducersmentioning
confidence: 97%
“…Experimentally, both the S-linked [46] and the O-linked [47] isomers have been previously characterized but in none of these studies, all carried out in solution, evidences of S/O (or O/S) linkage isomerization were found.…”
Section: Photo-triggered Isomerization Of [Ru(bpy)(tpy)dmso] + : Expementioning
confidence: 99%
“…A Figura 2 exemplifica duas formas de obtenção de um metalopolímero [25]: (1) no polímero já sintetizado, coordena-se o complexo metálico, e (2) o complexo metálico que contém os iniciadores (I) reage com o monômero iniciando a polimerização. Essas duas reações produzem metalopolímeros.…”
Section: Photolysis Of Complex 3 Leads To Cis-[ru(bpy)unclassified
“…Muito progresso tem sido alcançado no desenvolvimento de metalopolímeros contendo o metal com o macroligante [25,26]. Entretanto, ainda se faz necessário que novas metodologias sejam estabelecidas para o preparo de ligantes funcionalizados tais como monômeros funcionalizados [27] e ligações destes aos metais.…”
unclassified
See 1 more Smart Citation